In Vitro demonstration of Pseudomonas Growth and Phenotypic Examinations of the Cells Under Cold Shock - Moumita, Anika Bushra; Tabassum, Nafisa; Nur, Ifra Tun (Bangladesh Journal of Microbiology, 2019)
The present study attempted to detect the effect of cold shock on Pseudomonas aeruginosa, P. fluorescence, and P. putida; to deduce the culturable cells, the possible dead cells and viable but non-culturable (VBNC) cells; i. e., living but not capable of forming the colony forming units (CFUs) at 0 oC and at 4 oC. Estimation of VBNC at low temperature was performed by deducting the number of culturable cells (formed as CFUs) at 0 °C and at 4 oC from the culturable cells at 37 °C. Maximum culturable cells (around 106 CFU/ ml) appeared at 24-48 hours, and after that, a gradual decline in the numbers of the culturable cells was observed. A minor but significant growth reduction was noticed in Minimal Broth compared to that in Luria Broth. Significant reduction in the culturable cells of all three strains was noticed under cold shock. However, a fraction of the population of each strain was observed to survive under cold stress. Interestingly while the number of culturable cells decreased in course of time under cold shock, the number of VBNC apparently seemed to be constant or to be increased. A comparatively lower number of VBNC was noticed under cold shock in case of P. putida which in turn affected culturability at ambient temperature. Bangladesh J Microbiol, Volume 34 Number 2 December 2017, pp 119-124